Dye-modified carbon nanotubes for the optical detection of amines vapours - Banimuslem, Hikmat; Hassan, Aseel; Basova, Tamara; Esenpinar, Aliye Asli; Tuncel, Sinem; Durmuş, Mahmut; Gürek, Ayşe Gül (Elsevier Science Sa, 2015)
Thin films of peripheral and non-peripheral tetra-substituted copper phthalocyanines [CuPcR4, R =-O(CH2CH2O)(3)CH3 or -S(CH2CH2O)(3)CH3] and their hybrids with single walled carbon nanotubes( SWCNT) have been investigated as optical active layers for amines vapours detection. Adsorption of amines onto the films' surfaces has been realized by monitoring changes in the phase shift (Delta(lambda)) of total internal reflection ellipsometry spectra. Methylamine has shown higher sensitivity and lower response time among the studied three amines. The steric hindrance provided by the shapes of the secondary and tertiary amine molecules is thought to decrease the interaction with films' surfaces as compared to methylamine. For all active layers used in this study, the sensitivity of SWCNT/CuPcR4 hybrid films was higher than the sensitivity of pristine CuPcR4 films with clear recovery in the Delta(lambda) spectra after flushing the cell with air. The lower response time at 40 ppm is found to be 66 s and the highest sensitivity is 0.000325/ppm towards methylamine vapour. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Metal phtalocyanine; Single-Walled Carbon Nanotubes; TIRE; Amines detection